2022
DOI: 10.1002/fft2.135
|View full text |Cite
|
Sign up to set email alerts
|

Onion (Allium cepa L.) bioactives: Chemistry, pharmacotherapeutic functions, and industrial applications

Abstract: Bioactive compounds possess different health benefits. Onion contains various bioactive compounds, such as organosulfur compounds, flavonols, ascorbic acids, and carbohydrate prebiotics, and its by‐products have more content of flavonoids than the bulb. Diallyl monosulfide, diallyl disulfide, diallyl trisulfide, and diallyl tetrasulfide are the major organosulfur compounds, whereas quercetin, kaempferol, anthocyanin, and luteolin are considered as main flavonoids. Ascorbic acid and fructooligosaccharides are a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
48
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(48 citation statements)
references
References 275 publications
0
48
0
Order By: Relevance
“…Red onion husks had the highest contents of polyphenols, followed by the yellow onion husks, with the white onion containing the lowest amounts [ 36 , 47 , 48 ], but in our study no compounds were detected in the white onion husk extracts. It was reported that white onions contained trace amounts of total quercetin [ 37 ], but it was detected in husks, albeit in much lower concentrations than in red and yellow ones [ 11 , 14 ]. Quercetin and myricetin, found in large quantities in red and yellow onion husk extracts, are the main representatives of flavonols, which are considered to be the most abundant type of flavonoids in foods.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Red onion husks had the highest contents of polyphenols, followed by the yellow onion husks, with the white onion containing the lowest amounts [ 36 , 47 , 48 ], but in our study no compounds were detected in the white onion husk extracts. It was reported that white onions contained trace amounts of total quercetin [ 37 ], but it was detected in husks, albeit in much lower concentrations than in red and yellow ones [ 11 , 14 ]. Quercetin and myricetin, found in large quantities in red and yellow onion husk extracts, are the main representatives of flavonols, which are considered to be the most abundant type of flavonoids in foods.…”
Section: Discussionmentioning
confidence: 99%
“…More than 550,000 tons of bio-waste are generated during onion processing [ 5 , 6 ], which consists of peeling, slicing, and dicing, and these operations generate a large amount of waste [ 11 ]. Interest in onion waste has grown significantly in recent years, as evidenced by the increase in the number of related scientific studies in the past 2 years.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Onion (Allium cepa L.) is ubiquitously used as flavorful and healthy food, not to mention its remarkable medicinal properties, both preventive and curative. Onions also possess anti-cancer properties due to the accumulation of a number of bioactive compounds, including organosulfur compounds (review [22]), as well as antibiotic, anti-inflammatory, antiplatelet, antidiabetic, and cardio protective properties (review [23]). In terms of global production value, onion is ranked second after tomato (www.fao.org/faostat).…”
Section: Introductionmentioning
confidence: 99%